9th zoom course: the most-awaited yearly radiology department’s radiograph revision course - Mohd Arifin, Natasha; Abdul Kadir, Roqiah Fatmawati; Ab Mumin, Nazimah (Faculty of Medicine, 2022)
The ZOOM radiograph revision course is one of the most awaited yearly events for the Department of Radiology Universiti Teknologi Mara, the brainchild of Dr. Mohammad Hanafiah Kreah and Assoc. Prof. Dr. Bushra Johari back i n 2014. The main focus of this course is for the trainee radiologists to develop skills and confidence in performing their viva voce, which is a part of the compulsory exit examination. The participants were the Master of Radiology (MRad) and Fellowship of Royal College of Radiologists (FRCR) candidates from all over Malaysia.